Stock market conditions and profitability of momentum long-short arbitrages in the U.S.A. REITS market : 1972-2008. - Chew, Jinfeng. (2009)
Motivated by earlier studies on momentum profitability in REITs in the U.S.A for the period 1972-2000, this research investigates profitability of {3,3} and {6,6} momentum arbitrage portfolios in different stock market conditions for the extended time period from 1972-2008. Winner’s dividend/price ratios were found to be significantly lower than losers’ dividend/price ratio and dividend/price ratios of REITs are significantly higher after the legislation change in 1992. Our main findings are as follows: (1) Momentum returns of past winners are not significantly higher than past losers, in fact past losers had significantly higher momentum returns than losers; (2) Momentum returns are significantly higher during down markets; (3) There is a positive relationship between momentum returns in REITs and the difference between winners’ and losers’ dividend/price ratios and lastly (4) Momentum returns are not significantly higher after the legislation change in 1992.